Nanocrystalline Iron Pyrophosphate-Regulated Amorphous Phosphate Overlayer for Enhancing Solar Water Oxidation - Xia, Chengkai; Li, Yuankai; Je, Minyeong; Kim, Jaekyum; Cho, Sung Min; Choi, Chang Hyuck; Choi, Heechae; Kim, Tae‑Hoon; Kim, Jung Kyu (Nano-Micro Letters, 2022)
A rational regulation of the solar water splitting reaction pathway by adjusting the surface composition and phase structure of catalysts is a substantial approach to ameliorate the sluggish reaction kinetics and improve the energy conversion efficiency. In this study, we demonstrate a nanocrystalline iron pyrophosphate (Fe4(P2O7)3, FePy)-regulated hybrid overlayer with amorphous iron phosphate (FePO4, FePi) on the surface of metal oxide nanostructure with boosted photoelectrochemical (PEC) water oxidation. By manipulating the facile electrochemical surface treatment followed by the phosphating process, nanocrystalline FePy is localized in the FePi amorphous overlayer to form a heterogeneous hybrid structure. The FePy-regulated hybrid overlayer (FePy@FePi) results in significantly enhanced PEC performance with long-term durability. Compared with the homogeneous FePi amorphous overlayer, FePy@FePi can improve the charge transfer efficiency more significantly, from 60% of FePi to 79% of FePy@FePi. Our density-functional theory calculations reveal that the coexistence of FePi and FePy phases on the surface of metal oxide results in much better oxygen evolution reaction kinetics, where the FePi was found to have a typical down-hill reaction for the conversion from OH* to O2, while FePy has a low free energy for the formation of OH*. Highlights: 1 Inducing a localized crystalline iron pyrophosphate in amorphous iron phosphate overlayer. 2 Enhanced photoelectrochemical water oxidation activity with long-term durability. 3 The heterogeneous hybrid structure overcoming the energy barrier in water oxidation.